2021
DOI: 10.1186/s13075-020-02400-y
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic and high-frequency ultrasound imaging of systemic sclerosis patients

Abstract: Introduction Systemic sclerosis starts with an early phase characterized by Raynaud’s phenomenon, puffy fingers/hands, autoantibodies, and a scleroderma nailfold microscopic pattern. Alterations in the nailfold microscopic pattern are not evident in all early SSc patients. Photoacoustics (PA) and high-frequency ultrasound (HFUS) could fulfill this need. The former can measure oxygen saturation while the latter can measure skin thickening. We hypothesize that photoacoustics and high-frequency ul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…There are a limited number of studies investigating the vasculopathy of patients with SSc 15 18 ; some studying the microvasculature rather than larger vessels. Both Eisenbrey et al 17 and Daoudi et al 18 focused on high resolution imaging in the fingertip observing and measuring capillaries in the nailbed where microvascular abnormalities are known to occur. Eisenbrey et al 17 measured nailbed oxygenation in patients with SSc (N = 7) and controls (N = 15) before and after cold challenge (15 °C for 1 min).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are a limited number of studies investigating the vasculopathy of patients with SSc 15 18 ; some studying the microvasculature rather than larger vessels. Both Eisenbrey et al 17 and Daoudi et al 18 focused on high resolution imaging in the fingertip observing and measuring capillaries in the nailbed where microvascular abnormalities are known to occur. Eisenbrey et al 17 measured nailbed oxygenation in patients with SSc (N = 7) and controls (N = 15) before and after cold challenge (15 °C for 1 min).…”
Section: Discussionmentioning
confidence: 99%
“…A larger decrease in oxygenation level in the SSc group following cold challenge could be used to discriminate between patients with SSc and controls (area under the ROC curve = 0.91) 17 . Daoudi et al 18 imaged, again at the nailbed, 17 patients with SSc, 5 primary Raynaud’s phenomenon and 9 healthy controls. Both studies identified differences between patients with SSc and those without microvascular involvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For clinicians or radiologists, “seeing is believing”. In the last several years, several clinical studies on PAT/US dual-modality were reported, including human thyroid ( Dima and Ntziachristos, 2016 ; Yang et al, 2017 ; Kim et al, 2021 ), breast ( Garcia-Uribe et al, 2015 ; Becker et al, 2018 ; Neuschler et al, 2017 ; Nyayapathi and Xia, 2019 ; Kelly et al, 2020 ; Goh et al, 2019 ; Yang et al, 2020 ), skin ( Oraevsky et al, 2018 ; Park et al, 2021 ), extremities ( Xia et al, 2015 ; Mercep et al, 2015 ; Liu and Zhang, 2016 ; Kim et al, 2016 ; Jo et al, 2017 ; Oeri et al, 2017 ; van den Berg et al, 2017 ; Feng et al, 2020 ; Daoudi et al, 2021 ), prostate ( Agrawal et al, 2020 ; Kothapalli et al, 2019 ), bowels ( Knieling et al, 2017 ; Leng et al, 2018 ; Yang et al, 2019 ), vascular ( Karpiouk et al, 2012 ; Wu et al, 2015 ; Andrei et al, 2021), placenta ( Xia et al, 2015 ; Maneas et al, 2020 ) and others ( Jose et al, 2009 ; Gonzalez et al, 2021 ; Mozaffarzadeh et al, 2021 ). With the combination of the two modalities in one imaging system, it is acceptable for radiologists or clinicians to adapt and associate morphological features with functional information.…”
Section: Clinical Applications Of Pat/us Systemmentioning
confidence: 99%
“…However, this work has not provided a quantitative assessment based on trabecular bone PAT signal. And then, MSOT/US was applied for assessment of 17 systemic sclerosis (SSc) patients (5 out of 17 was in early phase) with nailfold damage, 5 primary Raynaud’s phenomenon (PRP) and 9 health controls ( Daoudi et al, 2021 ). Since MOST can quantitatively evaluate capillary density and hemoglobin (Hb) contents of the third fingers and US is capable of measure skin thickness of the lesions, this hybrid method could help to distinguish early SSc from PRP individuals and health controls in both Hb contents and skin thickness.…”
Section: Clinical Applications Of Pat/us Systemmentioning
confidence: 99%